β 2 -microglobulin inhibits Escherichia coli biofilm formation via selectively blocking curli assembly - Harshita Agarwal; Harita Ben; Amlan Chaini; Bharat Gurnani; Nabanita Mukherjee; Arumay Pal; Arun Kumar Upadhyaya; Surajit Ghosh; Dibyendu Kumar Sasmal; Neha Jain (Proceedings of the National Academy of Sciences, 2026)
Bacteria have evolved a remarkable strategy to thrive in hostile environments by creating well-organized microcommunities known as biofilms. Biofilms pose a serious global health challenge due to their contribution to antibiotic resistance and suppression of the effectiveness of immune responses, thereby exacerbating pathogenic conditions. Biofilm-dwelling bacteria are difficult to eliminate since the cells are embedded within a self-produced, intricate 3D extracellular matrix composed of protein polymers (amyloids), polysaccharides, and extracellular nucleic acids. The robustness of the matrix poses a significant challenge to curb biofilm infections. Moreover, there is a lacuna in understanding how biofilm may be controlled under physiological conditions. Therefore, it is imperative to investigate the role of host proteins in keeping a check on biofilm formation. In the present study, we have established β 2 -microglobulin (β 2 m), a human protein integral to innate immunity, as a potent inhibitor of biofilm formation in Escherichia coli . Our comprehensive biophysical, biochemical, computational, microscopic, and in vivo analyses revealed that β 2 m effectively prevents E. coli biofilm formation by specifically inhibiting amyloid curli, a major matrix component of E. coli biofilm. In a rat skin wound infection model, β 2 m significantly accelerated wound healing, underscoring its therapeutic potential against biofilm infections. Our results illustrate a crucial function of β 2 m as an endogenous antibiofilm and anticurli protein, provides a host-derived strategy to combat biofilm infections, and presents a method to augment existing antimicrobial therapies.